2012
DOI: 10.1007/s00401-012-0981-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct disease-risk groups in pediatric supratentorial and posterior fossa ependymomas

Abstract: Purpose No reliable classification exists for the therapeutic stratification of children with ependymoma, such that disease-risk might be identified and patients treated to ensure a combination of maximal cure rates and minimal adverse therapeutic effects. This study examined associations between clinicopathological and cytogenetic variables and outcome in a trial cohort of children with ependymoma, with the aim of defining a practical scheme for grading this heterogeneous tumor. Methods Intracranial ependym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 35 publications
9
85
0
6
Order By: Relevance
“…The WHO classification includes pathological variations of ependymoma grouped like this: grade I with Myxopapillary and subependymoma variant, the classic tumor grade II (clear cells, tanacitic and papillary variants) and grade III anaplastic type. There are reported differences between infratentorial and supratentorial ependymomas, it was observed that the pathological classification does not correlate with the anatomical location and the clinical results [1]. Relevant cytogenetic abnormalities found in anaplastic ependymomas (AE) are the 1q chromosome gain, anomalies in copies of chromosomes 6q25 (LATS1), 9p21 (CDKN2A), 11q.13 (generates the fusion protein C11ORF95-RELA).…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The WHO classification includes pathological variations of ependymoma grouped like this: grade I with Myxopapillary and subependymoma variant, the classic tumor grade II (clear cells, tanacitic and papillary variants) and grade III anaplastic type. There are reported differences between infratentorial and supratentorial ependymomas, it was observed that the pathological classification does not correlate with the anatomical location and the clinical results [1]. Relevant cytogenetic abnormalities found in anaplastic ependymomas (AE) are the 1q chromosome gain, anomalies in copies of chromosomes 6q25 (LATS1), 9p21 (CDKN2A), 11q.13 (generates the fusion protein C11ORF95-RELA).…”
Section: Reviewmentioning
confidence: 99%
“…Relevant cytogenetic abnormalities found in anaplastic ependymomas (AE) are the 1q chromosome gain, anomalies in copies of chromosomes 6q25 (LATS1), 9p21 (CDKN2A), 11q.13 (generates the fusion protein C11ORF95-RELA). A group was established that included patients with the following clinical-molecular profile: very young by age, recurrent tumor located in the posterior fossa and the 1q gain that is related -independently-with a worse prognosis and a strong predictor of adverse outcomes [1,2]. The alteration in the chromosomes 6q25 (LATS1), 9p21 (CDKN2A) was found infrequently.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations